Typification of colombian specimens of Lutzomyia longipalpis (Diptera: Psychodidae) by “Barcoding” - HOYOS L., RICHARD; URIBE S., SANDRA; VÉLEZ, IVÁN (Revista Colombiana de Entomología, 2012)
Lutzomyia longipalpis, is the main vector of visceral leishmaniasis in the Neotropic and the taxonomic identification is relevant for epidemiologic studies and for the disease control. The evidence supporting the existence of a L. longipalpis species complex morphologically indistinguishable besides similarity with females belonging the Lutzomyia subgenus and longipalpis series, difficult taxonomical identification when there are not available males. In this study, we used the sequence proposed worldwide as DNA barcode to distinguish animal species to characterize specimens belonging to L. longipalpis from three Colombian localities (Neiva, El Callejón, Girón) and evaluate their usefulness in separating them from closely related species such as L. gomezi, L. cruciata and L. bifoliata. The amplified and sequenced fragment exhibited a length of 548 bp and 26 haplotypes for 33 individuals of L. longipalpis, one haplotype for L.gomezi, one haplotype for L. cruciata and two haplotypes for L. bifoliata were found. Genetic distances (K2P) between L. longipalpis haplotypes (0.05-0.07) and clusters in a NJ dendrogram, effectively separated L. longipalpis from individuals belonging to closely related species. Individuals of L. longipalpis were separated in two groups, one included haplotype from Neiva and El Callejón, and the other from Girón. The genetic distance found between the two groups of L. longipalpis were significantly higher than those found at the intraspecific level for species previously studied on the basis of the barcode sequence as L. trinidadensis (0.042) and L.panamensis (0.02).